Perdata Analisis Yuridis Terhadap Sengketa Hak Asuh Anak Dalam Perkara Perceraian di Indonesia Berdasarkan Hukum Acara Perdata: Analisis Yuridis Putusan Pengadilan dalam Sengketa Hak Asuh Anak - Oktaviani, Silvia Nur; Desiana, Annisa Rifka; Atmojo, Turino Ferdian; Siswajanthy, Farahdinny; Butar Butar, Dinalara D (PUSAT SAINS INDONESIA, 2025)
Divorce is a legal event with far-reaching effects, not only on the couple, but also on the children who are part of the family. One of the most intricate impacts is the emergence of child custody disputes (hadhanah), which frequently become the primary focus in the judicial process. The objective of this article is to undertake a juridical analysis of the settlement of child custody disputes in divorce cases based on Indonesian civil procedural law. The present research employs a normative juridical method, characterized by a statutory approach and an examination of pertinent literature. The results indicate that, despite the existence of positive legal regulations in Indonesia, specifically Law No. 1/1974 on Marriage, the Compilation of Islamic Law (KHI), and Law No. 35/2014 on Child Protection, the implementation of these laws in practice continues to encounter significant challenges. These findings indicate a necessity for an adaptive approach to civil procedural law and the synchronization of legal regulations to ensure the protection of children's interests in the divorce legal process.